Clinical and Imaging Outcomes After Combined Direct and Indirect Bypass for Pediatric Moyamoya Disease: A Single Center Retrospective Series. (1st September 2019) - Morshed, Ramin A; Murph, Daniel; Dao, Jasmin; Colao, Kathleen; Avalos, Lauro; Hetts, Steven; Abla, Adib A; Fox, Christine; Lawton, Michael T; Gupta, Nalin
Abstract: INTRODUCTION: Moyamoya disease is a progressive cerebrovascular arteriopathy of unknown etiology, causing narrowing and eventual occlusion of the internal carotid arteries and their branches. Surgical revascularization is a key component of the overall treatment strategy. The goal of this study was to determine outcomes and complications related to direct vascular bypass in a pediatric cohort with Moyamoya disease. METHODS: All pediatric patients (<18 yr of age) treated with direct bypass combined with encephalomyosynangiosis between 2006 and 2017 at the authors' institution were included in the cohort. Demographic features, treatment, and outcomes were determined retrospectively from clinical reports available through the electronic medical record. RESULTS: A total of 18 patients (11 females and 7 males) underwent 32 bypass procedures with a median follow-up of 2.2 yr (range 22 d 8.6 yr). Mean age at operation was 8.3 yr (range 1.4-16.9 yr). Preoperative Suzuki stage 1, 2, 3, 4, and 5 were seen in 2, 7, 7, 12, and 4 hemispheres, respectively. By last follow-up, 3 patients had evidence of new clinical ischemic stroke, all occurring within 30 d of surgery. Favorable outcomes (pediatric modified Rankin scores 0-2) at last follow-up were seen in 15 patients (83.3%). There was 1 death in the cohort due to gastrointestinal bleeding related to underlying medical comorbidities. On review of imaging at last follow-up for surviving patients, 29 of 30 direct arterial bypasses were patent; 12 and 5 patients had stable and worse imaging findings, respectively, when compared to immediate postoperative scans. CONCLUSION: Combined direct and indirect revascularization procedures may be successfully applied to pediatric patients with Moyamoya disease of all age groups. The direct bypass component provides immediate revascularization and is associated with high rates of patency on follow-up imaging.